The civilizational return of Eastern “Rites and Music” and Western “Ethics” in modern music education - Li, Li (2024)
Civilization is a symbol of culture, and only music education with the spirit of civilization has the core of culture. To meet the needs of the times and promote the reform of the educational system, this study analyzes the Eastern rites and music civilization, and Western ethical civilization. The similarities and differences between them were compared. It was found that both affirm the moral-emotional-aesthetic value of music, but they consider the internal and external nature of its role different. The philosophical foundations of the music education system in modern society are analyzed, and the current state of music education is reflected. Aiming at the problems of lack of subjectivity, lack of understanding and lack of musical identity in music education, the study proposes an innovative path for modern music education in the way of the return of the civilizations of oriental “rites and music” and western “ethics,” i.e., resetting the norms of the musical grammatical behavior, penetrating the humanistic connotations and defining the position of subjectivity.